PHYTOCHEMICAL SCREENING AND POLYPHENOL EXTRACTION FROM Musa balbisiana CORM - Nguyen Quang Liem; Ho Le Bao Ngoc; Ha Thi Minh Thu; Nguyen Pham Khanh Linh; Hoang Thi Ngoc Nhon (HUIT Journal of Science, 2024)
The extraction and characterization of the components of Musa balbisiana corm were carried out to identify biologically active compounds, such as saponins, flavonoids, tannins, and carotenoids... Among these compounds, polyphenols were found to be the most prevalent in banana corm extracts, and they have been shown to possess a wide range of biological activities, including antioxidant, antibacterial, anti-mold, and hypoglycemic properties, etc. These findings suggest that polyphenols derived from banana corm have great potential for use in the fields of medicine and pharmaceuticals. To optimize the extraction of polyphenols from banana corm, various factors need to be investigated, including the type of solvent (ethyl acetate, ethanol, and water), solvent concentration (60; 70; 80; 90; 99.5%), solid-to-liquid ratio (1/10; 1/20; 1/30; 1/40; 1/50, w/v), temperature (40; 50; 60; 70; 80 °C), and time (30; 60; 90; 120; 150 min). Results from the research indicate that ethanol is the most suitable solvent for extracting polyphenols from banana corm. The highest polyphenol content was obtained under optimal conditions, which included 82.05% ethanol concentration, a material-to-solvent ratio of 1/30 w/v, and an extraction temperature of 61.64 °C for 97.88 min, yielding 62.84 mgGAE/gCK.